Discovery of 3-alkyl-5-aryl-1-pyrimidyl-1H-pyrazole derivatives as a novel selective inhibitor scaffold of JNK3 - Youri Oh; Miyoung Jang; Hyunwook Cho; Songyi Yang; Daseul Im; Hyungwoo Moon; Jung-Mi Hah (Taylor & Francis Group, 2020)
3-alkyl-5-aryl-1-pyrimidyl-1H-pyrazole derivatives were designed and synthesised as selective inhibitors of JNK3, a target for the treatment of neurodegenerative diseases. Following previous studies, we have designed JNK3 inhibitors to reduce the molecular weight and successfully identified a lead compound that exhibits equipotent activity towards JNK3. Kinase profiling results also showed high selectivity for JNK3 among 38 kinases. Among the derivatives, the IC50 value of 8a, (R)-2-(1-(2-((1-(cyclopropanecarbonyl)pyrrolidin-3-yl)amino)pyrimidin-4-yl)-5-(3,4-dichlorophenyl)-1H-pyrazol-3-yl)acetonitrile exhibited 227 nM, showing the highest inhibitory activity against JNK3.